Orthodontic treatment need for Brazilian schoolchildren: a study using the Dental Aesthetic Index - Anderson Barbosa de Almeida; Isabel Cristina Gonçalves Leite (Dental Press Editora, 2013)
OBJECTIVE: To determine the normative orthodontic treatment need among 12-year-old Brazilian schoolchildren, in the municipality of Juiz de Fora, Minas Gerais, Brazil, and compare with the need as perceived by the children themselves and their parents or caregivers, assessing putative associated sociodemographic factors. METHODS: Four hundred and fifty one children without a previous history of orthodontic treatment were randomly selected from a population of 7,993 schoolchildren regularly attending the public and private educational sectors of the municipality of Juiz de Fora, Minas Gerais, Brazil. RESULTS: The prevalence of normative orthodontic treatment need in 12-year-old children, assessed with the Dental Aesthetic Index (DAI) was 65.6% (n = 155). The need perceived by the caregivers was 85.6%, and by the children was 83.8%. Only the perception by the caregivers maintained a significant correlation with the normative need of treatment when adjusted to the parents' schooling and economical level (p = 0.023). CONCLUSIONS: There is a high prevalence (65.6%) of malocclusion requiring orthodontic treatment in 12-year-old Brazilian schoolchildren. The most prevalent malocclusions in the study were: Crowding, Class II molar relationship and increased overjet. There was no significant correlation between the Index of Orthodontic Treatment Need - Aesthetic Component (IOTN-AC) related to dental aesthetic perception and the normative treatment need assessed with the DAI. OBJETIVO: determinar a necessidade normativa de tratamento ortodôntico em escolares brasileiros de 12 anos de idade, no município de Juiz de Fora, Minas Gerais, e compará-la à necessidade percebida pelos responsáveis e crianças da amostra, avaliando potenciais fatores sociodemográficos associados. MÉTODOS: quatrocentos e cinquenta e uma crianças, sem história de tratamento ortodôntico, foram selecionadas, aleatoriamente, de uma população de 7.993 escolares matriculados na rede de ensino pública e particular da cidade de Juiz de Fora. RESULTADOS: a prevalência da necessidade normativa de tratamento ortodôntico em crianças de 12 anos de idade, utilizando o Índice de Estética Dentária (DAI), foi de 65,6% (n = 155). A percepção da necessidade pelos responsáveis foi de 85,6% e pelas crianças foi de 83,8%. No entanto, somente a percepção dos responsáveis teve uma correlação significativa com a necessidade normativa (p = 0,023). CONCLUSÕES: existe uma alta prevalência (65,6%) de má oclusão com necessidade de tratamento ortodôntico em escolares brasileiros de 12 anos de idade. As más oclusões mais prevalentes no estudo foram apinhamento, relação molar de Classe II e sobressaliência maxilar. Não houve uma correlação significativa entre a percepção da estética dentária por meio do IOTN-AC (Index of Orthodontic Treatment Need) e a necessidade de tratamento normativo avaliada por meio do DAI.